Integrated fault-tolerant control of a quadcopter UAV with incipient actuator faults - Kantue, Paulin; Pedro, Jimoh O. (Zielona Góra: Uniwersytet Zielonogórski)
An integrated approach to the fault-tolerant control (FTC) of a quadcopter unmanned aerial vehicle (UAV) with incipient actuator faults is presented. The framework is comprised of a radial basis function neural network (RBFNN) fault detection and diagnosis (FDD) module and a reconfigurable flight controller (RFC) based on the extremum seeking control approach. The dynamics of a quadcopter subject to incipient actuator faults are estimated using a nonlinear identification method comprising a continuous forward algorithm (CFA) and a modified golden section search (GSS) one.
Keywords: fault-tolerant control; quadrocopter; incipient actuator fault; radial basis function neural network